Aberrant cortical neurodevelopment in major depressive disorder - Schmitgen, Mike; Depping, Malte S.; Bach, Claudia; Wolf, Nadine D.; Kubera, Katharina Maria; Hirjak, Dusan; Wolf, Robert Christian (Journal of affective disorders, 2019)
Background - There is strong neuroimaging evidence that cortical alterations represent a core pathophysiological feature of major depressive disorder (MDD). Differential contributions of cortical features of neurodevelopmental origin, which may distinctly contribute to MDD vulnerability, disease-onset, or symptom expression, are unclear at present. - Methods - We investigated distinct markers of cortical neurodevelopment, i.e. local cortical gyrification (LGI) and thickness (CT) in patients with MDD (n=38) and healthy controls (HC, n=22) using 3 T structural magnetic resonance imaging data and surface-based data analysis techniques. CT and LGI were computed using the Computational Anatomy Toolbox (CAT12). Analyses were performed for the entire cortical surface followed by a complementary regions-of-interest approach. - Results - MDD patients showed significantly greater LGI in frontal, cingulate, parietal, temporal, and occipital regions compared to HC (FDR-corrected at p<0.05 using threshold-free cluster enhancement). No significant differences of CT were found. In the MDD-group, correlations were found between duration of illness in years and number of depressive episodes and LGI of frontal, temporal, and parietal regions (p<0.05). - Limitations - Main limitations are the relatively modest sample size and a cross-sectional study design. We did not control for early environmental factors potentially influencing neurodevelopment, such as childhood trauma. We report associations uncorrected for multiple comparisons. - Conclusions - The data suggest different local trajectories of cortical change in MDD. In addition, our data support the notion that aberrant cortical development may serve as a vulnerability marker of MDD, as well as a potential predictor of disease course.
Available online 11 September 2018
Gesehen am 29.03.2019